Shelf Life of Biofilm Producing PGPR Liquid Inoculants in Different Enriched Media Composition - Rahma Tia Harahap; Isnaniar Rahmatul Azizah; Diyan Herdiyantoro; Mieke Rochimi Setiawati; Tualar Simarmata (Agro Bali : Agricultural Journal, 2023)
Selecting a carrier material compatible with microbes is crucial for ensuring the quality of biofertilizers. This research aimed to identify a carrier material that could sustain the population of inoculants from dryland (including Delftia tsuruhatensis strain D9, Delftia sp. strain MS2As2, and Bacillus sp.) for a specified period. After conducting the study, it was found that a formulation of 3% molasses, 3% glycerol, 1% potassium sorbate, and 1% Tween-20 enriched with 1% nutrient was the most effective carrier material in maintaining the number of live inoculant cells. This formulation was able to sustain the population of inoculants up to the twelfth week, with a total population of 21.60 × 108 CFU.mL-1 with pH value of media is 5.29, and fulfilled the main criteria for biofertilizers.